Trust in government as a mediator in the relationship between AI implementation and citizen satisfaction: Evidence from UAE Policing - Mohamad, Effendi; Saeed Ali Alhefaity, Shamsah Rashid; Jamli, Mohamad Ridzuan; Ito, Teruaki; Larasati, Aisyah; Mohamad, Nor Akramin (Malque Publishing, 2026)
This study investigates the influence of Artificial Intelligence (AI) implementation on citizen satisfaction with police services in the United Arab Emirates (UAE), with a specific focus on the mediating role of trust in government. As smart policing initiatives expand under the UAE’s digital governance agenda, understanding how AI technologies shape public trust and service perceptions becomes increasingly critical for sustainable public engagement. A quantitative research design was adopted using a cross-sectional survey method. Data were collected from 365 police personnel within the Abu Dhabi Police across AI-enhanced, operational, and administrative units. Structural Equation Modeling (PLS-SEM) was employed to assess both direct and indirect relationships among AI implementation, trust in government, and citizen satisfaction. Validated scales and reliability checkswere used to ensure measurement accuracy. The results demonstrate that AI implementation has a significant positive effect on citizen satisfaction (β = 0.400, p < 0.001) and trust in government (β = 0.511, p < 0.001). Trust in government, in turn, significantly influences citizen satisfaction (β = 0.321, p < 0.001) and mediates the relationship between AI implementation and satisfaction (indirect effect β = 0.164, p < 0.001). These findings support the conceptual framework grounded in Public Value Theory and Expectation-Confirmation Theory, highlighting the importance of trust as a critical mechanism through which AI influences public attitudes toward policing services. This study offers actionable guidance for policymakers and law enforcement agencies seeking to integrate AI responsibly. Emphasis should be placed on transparency, citizen-centric design, and ethical AI governance to reinforce trust and ensure positive service experiences. AI strategies must be aligned with public expectations to sustain long-term satisfaction. The study contributes to emerging literature on digital public service delivery by empirically validating the mediating role of trust in government in AI-supported law enforcement. It is among the first to explore this dynamic in the context of UAE policing, offering region-specific insights into the interplay between technology, institutional trust, and citizen satisfaction.